A More Electric Aircraft Application: Starter/Generator - Kaya, Ufuk; Oksuztepe, Eyyup (Springer Nature, 2023)
The More Electric Aircraft (MEA) concept aims for more efficient, more reliable, and more environmentally friendly aircraft that come with an increased demand for electric power. The conventional electric power production system is not sufficient enough and needs to be improved. The relatively new starter/generator (SG) system comes forward with a better solution. It provides not only efficient generator operation but also starter operation is secured. In this study, a permanent magnet synchronous machine (PMSM) with flux-weakening operation is simulated as SG on MATLAB/Simulink environment, for required necessities of future SG machine design. The outcomes have shown that the SG design should be discussed as a whole system that consists of the SG, controller, and power electronics. Hence, the SG simulation on system level is highly recommended. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.
Keywords: Flux-weakening; More Electric Aircraft; PMSM; Speed control; Starter/generator